Υποτιτλισμός και σχολιασμός του υποτιτλισμού της τανιίας μικρού μήκους: "Ruby | Irish short film about love, life, anniversaries and strange gifts" - (:unkn) unknown (My University, 2023)
Η συγκεκριμένη πτυχιακή εργασία επικεντρώνεται στον υποτιτλισμό της ταινίας μικρού μήκους με τίτλο “Ruby | Irish short film about love, life, anniversaries and strange gifts”. Πιο συγκεκριμένα, μετά από την ενδελεχή ανάλυση του σκοπού και του είδους της ταινίας, εμβαθύνουμε στην στρατηγική και την μεθοδολογία που ακολουθήθηκε αναφορικά με την διαδικασία του υποτιτλισμού ενώ έπειτα παρουσιάζουμε τις τεχνικές και μεταφραστικές προκλήσεις που αντιμετωπίστηκαν κατά τη διαδικασία αυτή. Παρουσιάζονται, επίσης, λεπτομερώς και οι αποφάσεις που ελήφθησαν σχετικά με τις μεταφραστικές αυτές δυσκολίες που αντιμετωπίστηκαν, με βάση τις μεταφραστικές θεωρίες γνωστών ερευνητών στον τομέα της μετάφρασης.

This dissertation focuses on the subtitling from English to Greek of a short film titled “Ruby | Irish short film about love, life, anniversaries and strange gifts”. More specifically, after a detailed analysis of the genre and the skopos of the short film, we delve into the strategy and method followed regarding the subtitling process and present the technical or translation difficulties encountered during the process. Based on the translation theories of well-known researchers in the field of translation studies, such as Nord and Baker, the decisions made regarding the translation difficulties that were encountered during the process are also presented in detail.
Subtitling and commentary of the subtitling of the short film: "Ruby | Irish short film about love, life, anniversaries and strange gifts"
Keywords: υποτιτλισμός, σκοπός, μετάφραση, διαγλωσσικός υποτιτλισμός; subtitling, skopos, translation, interlingual translation